"A Mother of One's Own": An Analytic View of Object-Relationships in Adult Patients Raised in the Kibbutz. Issue 3 (3rd July 2018) - Shapira-Berman, Ofrit
Abstract: Child rearing practices in Israel's kibbutzim (from the 1920s to the 1980s) offer a unique opportunity to explore possible consequences of a particular type of early mother–infant relations. During this time in the kibbutzim, it was common that babies were not raised by their mothers as sole, or even major, caretakers. This practice was different from current Western cultural norms of child rearing. Winnicott's view of the role of the mother (1958 [1965 ]) is examined in light of the author's extensive experience as a psychoanalyst treating adults who were raised in the communal child-rearing system of the kibbutz . The author aims to reexamine the object relations of her patients raised in the kibbutz as manifested in the psychoanalytic process. Patient–analyst relations, transference and countertransference, the analytic "frame, " and the analyst's emotional presence are discussed and examined through two clinical cases illustrating various consequences of the communal child rearing.